Increased Placental Glucose Transport Rates in Pregnant Mice Carrying Fetuses with Targeted Disruption of Their Placental-Specific Igf2 Transcripts Are Not Associated with Raised Circulating Glucose Concentrations. (20th January 2011) - Petry, Clive J.; Evans, Mark L.; Wingate, Dianne L.; Ong, Ken K.; Reik, Wolf; Constância, Miguel; Dunger, David B.
Abstract : At the beginning of the third week of pregnancy, mouse fetuses with targeted disruption of their paternally-transmitted insulin-like growth factor 2 gene placental-specific transcripts have growth-restricted placentas but normal body weights due to upregulated placental nutrient transport. We assessed whether increased placental glucose transport rates were associated with raised maternal glucose concentrations by performing intraperitoneal glucose tolerance tests (ipGTT) in pregnant mice carrying knockout pups and comparing them with mice carrying genotype-matched phenotypically wild type pups. Mean ± SD body weights of affected pups were 95 ± 8% of control values at e16 and 73 ± 7% at e18. There were no differences in areas under the maternal ipGTT curves at either e16 (mean ± SD being 99.0 ± 9.1% of control values;P = .9 ) or e18 (91.4 ± 13.4%;P = .3 ), suggesting that effects on transplacental glucose transport in these mice are not mediated through changes in maternal glucose concentrations.